Difficulties in mathematics among students with Swedish as a second language: Teachers‘ views on difficulties, causes, and measures in mathematics in Swedish lower secondary school, with a focus on students with Swedish as their second language - Hanoun Santana, Daniella; Törnqvist, Johanna (My University, 2022)
In the media, news has highlighted that Sweden has performed worse in PISA (Programme for International Student Assessment) over the years compared to other countries. Statistics of Sweden’s results of mathematics in PISA and National Tests show that students with a language other than Swedish as their mother tongue generally perform with a lower result compared to the students with Swedish as their mother tongue. The study aims to investigate the understanding of mathematics among students with Swedish as a second language who study mathematics with Swedish as the language of instruction. The chosen method for this study is qualitative interviews, including seven respondents teaching mathematics at five Swedish lower secondary schools. Via the insight of the teachers’ perspective, this study answers the following questions; What specific difficulties do students with Swedish as a second language encounter in mathematics teaching? What factors contribute to the difficulties in mathematics learning that students with Swedish as a second language encounter? How do mathematics teachers in lower secondary schools work to make it easier for students with Swedish as a second language who have difficulties? The study is based on the sociocultural perspective which implies that students learn through interaction with each other so that learning takes place in social contexts. language comprehension; problem-solving tasks, mathematical concepts, reasoning, and This study shows that students with Swedish as a second language (SVA) encounter difficulties connected to communication. The causes of these difficulties according to the respondents are language comprehension, cultural differences, prior knowledge, and poor study technique. Common measures to facilitate the SVA students’ learning in mathematics are interaction, support in the mother tongue, image support, paying attention to the student’s culture, and increasing reading comprehension. These results are relevant for mathematics teachers who teach SVA students. By understanding the basic problem of the difficulties, teachers can take the right action and thus provide an equivalent education.
Keywords: Swedish as a second language; difficulties in mathematics; mathematical language; problem solving